Level of Anxiety-State as a factor in changing eating patterns in college students: NUTSAU Study (Research, Society and Development, 2021)
With the purpose of identifying eating patterns of university students at a federal university in the state of Rio de Janeiro, a cross-sectional analysis of food consumption data was stratified by anxiety symptom scores of 147 students enrolled in the second semester of several undergraduate courses in the second semester of 2015. The State-Trait Anxiety Inventory determined the anxiety symptoms scores. A food frequency questionnaire was applied to obtain food consumption data. Students were stratified into two groups, using the median state anxiety score as cutoff point. For each group, some dietary patterns were derived by the application of the principal component analysis. Statistical analysis was performed using the SPSS software. The university students presented a median state-anxiety score of 43 points, and it was significantly higher in women. Three dietary patterns were identified for each group according to their nutritional characteristics, among which “Mixed 1”, “Healthy” and “Rice and Beans” for the less anxious students and “Western”, “Mixed 2” and “Rice and Beans” for the most anxious students. The results showed that it was possible to identify consistent food patterns for both, using a factorial analysis method. Students with the highest anxiety-state scores had a pronounced Western eating pattern, and those least anxious students had higher consumption of healthier food groups and lower consumption of caffeinated beverages. Although this is a cross-sectional analysis, it can contribute to optimize nutritional intervention for this population.